2014
DOI: 10.1515/pac-2014-5042
|View full text |Cite
|
Sign up to set email alerts
|

3-Acyloxy-1,4-enyne: A new five-carbon synthon for rhodium-catalyzed [5 + 2] cycloadditions

Abstract: Seven-membered rings are ubiquitous in natural products and pharmaceutical agents and their syntheses continue to stimulate the development of novel synthetic methods. The (5+2) cycloaddition is one of the most efficient ways to access seven-membered rings since the 2-carbon components (alkenes, alkynes, or allenes) are readily available. Prior to our study, however, there was only one type of transition metal-catalyzed (5+2) cycloaddition: the reaction between vinylcyclopropanes and alkenes, alkynes, or allen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previously, we and others have demonstrated that 3-acyloxy-1,4-enyne 38 can serve as the five-carbon component in Rh-catalyzed [5 + 1] cycloaddition, and we also extended it to [5 + 2] cycloaddition , as shown in Scheme A. DFT calculations suggested a rhodium-mediated concerted oxidative cyclization accompanied by 1,2-acyloxy migration as shown in 39 for the formation of metallacycle 40 from ester 38 .…”
Section: Resultsmentioning
confidence: 74%
“…Previously, we and others have demonstrated that 3-acyloxy-1,4-enyne 38 can serve as the five-carbon component in Rh-catalyzed [5 + 1] cycloaddition, and we also extended it to [5 + 2] cycloaddition , as shown in Scheme A. DFT calculations suggested a rhodium-mediated concerted oxidative cyclization accompanied by 1,2-acyloxy migration as shown in 39 for the formation of metallacycle 40 from ester 38 .…”
Section: Resultsmentioning
confidence: 74%
“…Small cycloalkanes are critical for organic synthesis in medicinal chemistry, [4][5][6] and transition metal catalysts are sometimes utilized to obtain functional molecules from cycloalkanes as the starting point. Rhodium (I) catalyzes the cycloadditions [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] of vinyl-or allenylcycloalkanes. Reactants containing 3-membered, 4-membered, and 5-membered rings have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…13 The high degree of unsaturation and the enol ester functionality in cycloaddition product 9 are ideally set up for the synthesis of substituted tropone 10 . We herein report our efforts along this direction for the first time.…”
Section: Introductionmentioning
confidence: 99%